Enhancement of slurry dewatering in basket centrifuge using bypass filter medium - Ginting, Alvin Najmuddin; Fukuyama, Ryo; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
When centrifugal dewatering in basket centrifuge involves the sedimentation of particles in feed slurry, the slurry separates into two phases: supernatant and cake. The process of dewatering proceeds as the supernatant permeates through the cake. In the situation where the cake formed has poor permeability, it takes longer time to completely discharge the supernatant. It is known from the previous study [1] that once the supernatant is totally discharged, the cake will undergo a consolidation process, resulting in a less moist cake. Therefore, the discharge of the supernatant is important for an efficient dewatering. According to the current practice, the supernatant is discharged by either suction using a skimming pipe from the inner side of the basket or by increasing the rotational speed. However, these methods are not the perfect solutions because the skimming pipe method requires some distance to be kept between the pipe and the cake, and it is very inefficient to dewater highly compressible materials under high rotational speed.